The coin hoard of Abasár - Torbágyi, Melinda; Vida, István (Dissertationes Archaeologicae, 2013)
The composition of the small hoard found on the northern edge of the Great Plain is very interesting and unique in Hungary, as Celtic tetradrachms and small change were hidden along with Roman Republican and Imperial denarii. The peculiar composition of the hoard suggests the treasure was aggregated by several generations of the owner’s family. The silver ingot indicates that the hoard was treated as bullion rather than money, which attests the lack of regular coin circulation in the Celtic Carpathian basin. The Lapujtő type coins of the hoard denote eastern connections, they probably mark the arrival of Celts fled before the Dacians. The Roman coins might indicate the establishment of an ally system as a part of the Augustean foreign politics, and based on the coins it existed even during the reign of Tiberius.